ANALISIS PERSEPSI FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN PRODUK (STUDI PADA PEDAGANG KIOS BUKU SRIWEDARI) - Handaruwati, Indah (Widya Warta, 2016)
Sriwedari area was popular as the center of trade books. Book traders’s perception related to factors influencing book sales was needed associated with strategy and efforts held by Solo city government and book trader association to increase book sales. The objective of this research was to give empirical evidence about factors influencing book sales. Data collected by questionnaire were analyzed by ordinal logistic regression. The results show that bookstore discount, the collection of used books and the collection of new books significantly affected the book sales. While shop opening hours insignificantly affected the book sales.